THE APPLICATION OF THE PRINCIPLE OF DECENTRALISATION IN REGIONAL AUTONOMY - Kurniawan, Iwan; Djunaedi, O.; Akkapin, Supaphorn (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
The transformation of Indonesia's governance system through decentralization has granted extensive authority to local governments to manage administrative affairs based on their unique potentials and needs. The principle of decentralization aims to accelerate development and enhance community welfare through improved public services. However, the implementation of this principle faces numerous challenges, including regional development disparities, abuse of power, and suboptimal budget management. This study employs a juridical-normative approach to analyze the effectiveness of decentralization in regional autonomy, focusing on supervision, budget allocation, and the administrative capacity of local governments. The findings reveal that while decentralization has the potential to accelerate development, fiscal imbalances and weak supervision remain significant obstacles. Consequently, reforms in oversight systems and more transparent budget management, alongside enhanced local government capacity, are necessary to maximize the benefits of decentralization. The study recommends strengthening supervision, improving central-local coordination, and adjusting budget allocations to reduce regional development disparities. These measures are expected to help achieve the goals of decentralization in fostering equitable development and enhancing community welfare.